RELATION OF IMPLEMENTATION OF LEARNING COMPOSITES IMPROVING HIGH LEARNING SKILLS (HOTS) WITH STUDENTS’ ACHIEVEMENT IN ISLAMIC EDUCATION LESSONS - Mohd Syaubari Othman; Tajul Rosli Shuib; Mohamad Marzuqi Abd Rahim; Mohammad Zarkhuan Zainol; Ahmad Yunus Kassim (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
This study aims to see the relationship between the implementation of learning composition that integrates HOTS with the achievement of students through Islamic education subjects in primary schools. This study examines the profile of the aspect of student learning composition and the relationship with the current student achievement. The instrument used is the adaptation of the HOTS questionnaire which has adapted the modified Anderson instrument from Bloom's taxonomy, 'Learning and Study Strategies High Order Thinking, Islamic Education teaching practice assessment instrument by (Mohd Aderi, 2010) And teaching monitoring instructional materials (JNJK, 2011) to measure the implementation of student learning composition with the reliability value of Cronbach Alpha (α) 0.902. Samples involved were year five students who were taken randomly stratified and grouped from national schools around the state of Perak. The data were analyzed using frequency, percentage, mean, standard deviation, and Pearson correlation. The results showed that the level of correlation between the composition of learning and the achievement of the students was moderate high for six constructs ie planning (min = 3.43, SP = 0.54, r = 0.457), objective setting (min = 3.31, SP = 0.49, r = 0.455) The use of educational resources (mean = 3.35, SP = 0.48, r = 0.673), implementation of questionnaire (min = 3.32, SP = 0.57, r = 0.535) (Min = 3.07, SP = 0.59, r = 0.4781), while performing reflection (mean = 3.15, SP = 0.55, r = 0.0931) summarize the teaching content (mean = 3.34, SP = 0.60, r = 0.183) = Low relationship. The findings also showed that the composition of learning in terms of overall and student achievement was moderate (r = 0.031, p = 0.579, r = 0.0852). Therefore, the implementation of learning composition is related to student achievement, but there are other factors contributing to student achievement in Islamic education subjects. Penelitian ini bertujuan untuk melihat hubungan penerapan komposisi pembelajaran yang mengintegrasikan HOTS dengan prestasi belajar siswa melalui mata pelajaran Pendidikan Agama Islam di Sekolah Dasar. Penelitian ini mengkaji profil aspek komposisi belajar siswa dan hubungannya dengan prestasi belajar siswa saat ini. Instrumen yang digunakan adalah adaptasi angket HOTS yang telah mengadaptasi instrumen Anderson yang dimodifikasi dari taksonomi Bloom, 'Strategi Pembelajaran dan Pembelajaran High Order Thinking, instrumen penilaian praktik pengajaran Pendidikan Islam oleh (Mohd Aderi, 2010) dan bahan ajar pemantauan pembelajaran (JNJK, 2011) untuk mengukur keterlaksanaan komposisi belajar siswa dengan nilai reliabilitas Alpha Cronbach (α) 0,902. Sampel yang terlibat adalah siswa kelas lima yang diambil secara acak bertingkat dan dikelompokkan dari sekolah nasional di sekitar negara bagian Perak. Data dianalisis menggunakan frekuensi, persentase, mean, standar deviasi, dan korelasi Pearson. Hasil penelitian menunjukkan bahwa tingkat korelasi komposisi pembelajaran dengan prestasi belajar siswa tergolong sedang tinggi untuk enam konstruk yaitu perencanaan (min = 3,43, SP = 0,54, r = 0,457), penetapan tujuan (min = 3,31, SP = 0.49, r = 0.455) Penggunaan sumber daya pendidikan (mean = 3.35, SP = 0.48, r = 0.673), pelaksanaan angket (min = 3.32, SP = 0.57, r = 0.535) (Min = 3.07, SP = 0.59, r = 0,4781), saat melakukan refleksi (mean = 3,15, SP = 0,55, r = 0,0931) meringkas isi pengajaran (mean = 3,34, SP = 0,60, r = 0,183) = hubungan rendah. Hasil penelitian juga menunjukkan bahwa komposisi pembelajaran ditinjau dari keseluruhan dan prestasi belajar siswa tergolong sedang (r = 0,031, p = 0,579, r = 0,0852). Oleh karena itu pelaksanaan komposisi pembelajaran berkaitan dengan prestasi belajar siswa, namun ada faktor lain yang turut mempengaruhi prestasi belajar siswa pada mata pelajaran pendidikan agama Islam.